Оценка изменения термодинамических свойств подземных вод при подземном сжигании угля - Садовенко, И.А.; Инкин, А.В. (Наукові праці УкрНДМІ НАН України, 2014)
Розроблена математична модель теплоперенесення в пі-дземних водах покриваючих порід вугільного пласта при його спа-люванні. Для гірничо-геологічних умов ділянки "Ольхова Нижня" за допомогою програми чисельного моделювання ModFlow 2009 отримані параметри зміни розмірів і форми теплових аномалій, що формуються у водопроникних породах. A mathematical model of heat transport in groundwater which saturate the overlying rocks of the coal seam by burning it. For the geological site conditions "Olhova Nizhnyaya" using simulation ModFlow 2009 estimates of changes in the size and shape of thermal anomaly formed in permeable rocks above the roof of the coal seam, depending on the angle of his fall, and the stage of combustion.